Study of Multiwavelength Fiber Laser in a Highly Nonlinear Fiber - Awang, Noor Azura; Mohd Nadzar, Izzaty Haziqah (Journal of Science and Technology, 2016)
A multiwavelength fiber laser in linear and ring cavity have been successfully developed and demonstrated in numerical and experimental method. The multiwavelength fiber laser developed is incorporating with the nonlinearity of a short section of highly nonlinear fiber (HNLF) in order to suppress the homogeneous broadening effect of erbium-doped fiber amplifier (EDFA) within the gain medium. The performance aspects such as maximum number of lasing lines generated, maximum output power produced, wavelength span covered, maximum gain obtained, and signal-to-noise ratio have been successfully investigated and analysed. The linear cavity fiber laser is observed to have more number of lasing lines generated with higher output power and wider span of wavelength when compared to ring cavity fiber laser. The output spectrum from experimental method seems to have greater performance than numerical method where 11 lasing lines in the range from 1586 nm to 1596 nm with highest output power -22.40 dBm and SNR of 43 dB is obtained for experimental method while only 4 lines generated in 1595 nm to 1594 nm wavelength range with highest output power of 0.18 dBm and SNR of 75.42 dB.